Rannij period v ėvoljucii maturiditskogo učenija = The early period in evolution of the Maturidi doctrine - Muminov, A. K. (Chabaršy. Dintanu serijasy, 2015)
Early evolution of the maturidi doctrine in Samarkand remains the low-studied subject. Development of a subject in many respects depends on introduction to a scientific turn of new sources among which hand-written are main. This article is devoted to research of an initial stage of development of maturidi theology in Central Asia.